STUDI EVALUATIF KEBIJAKAN PEMERINTAH DALAM PENGELOLAAN SAMPAH DI KOTA BANJARBARU - Widiati (stiatabalong.ac.id, 2025)
This research examines the implementation of government policy on waste management in Banjarbaru City, South Kalimantan Province. The background of the study includes the importance of effective waste management to maintain environmental cleanliness and public health, as well as the challenges faced in implementing the policy. The research objectives are to evaluate the effectiveness of the waste management policy that has been implemented, identify the obstacles faced, and provide recommendations for policy improvement. The research method uses a qualitative approach with data collection through surveys to the community, interviews with 2 participants, namely waste management officers, and direct observation in the field, the data analysis technique in this study uses triangulation. The results showed that community participation was still low, the policies implemented were not effective, and there were obstacles in coordination between related agencies. Research recommendations include increasing the budget, human resource capacity, cross-sector coordination, and the adoption of more modern waste management technology. It is hoped that the results of this study can serve as a basis for improving waste management policies in Banjarbaru City and other cities facing similar problems. Keywords: Waste management, Government policies, Banjarbaru City